2021
DOI: 10.1186/s40359-021-00680-w
|View full text |Cite
|
Sign up to set email alerts
|

Measuring mental wellness among adolescents living with a physical chronic condition: a systematic review of the mental health and mental well-being instruments

Abstract: Background Globally, promoting mental health and well-being among adolescents has become a public health priority, especially for adolescents living with a physical chronic condition (CC), as research suggests they may be more at risk of developing mental health co-morbidities. Valid and reliable instruments are needed to measure and better understand mental health and mental well-being among adolescents living with a CC. To this end, we reviewed studies reporting on mental health and well-bein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 48 publications
0
19
0
2
Order By: Relevance
“…To answer the abovementioned questions, we conducted a systematic review of all instruments used to measure mental wellness in adolescents (Orth et al, 2022 ). The sub-analysis of instruments used among adolescents living with a chronic condition (Orth and van Wyk, 2021a ) revealed that Health-Related Quality of Life (HRQoL) instruments were frequently used to measure physical and psychosocial wellbeing among adolescents living with a physical chronic condition. However, these HRQoL instruments often include mental illness and mental wellness indicators which raises the question—to what degree is the absence of mental disorder symptoms equal to a high degree of mental wellness?…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To answer the abovementioned questions, we conducted a systematic review of all instruments used to measure mental wellness in adolescents (Orth et al, 2022 ). The sub-analysis of instruments used among adolescents living with a chronic condition (Orth and van Wyk, 2021a ) revealed that Health-Related Quality of Life (HRQoL) instruments were frequently used to measure physical and psychosocial wellbeing among adolescents living with a physical chronic condition. However, these HRQoL instruments often include mental illness and mental wellness indicators which raises the question—to what degree is the absence of mental disorder symptoms equal to a high degree of mental wellness?…”
Section: Methodsmentioning
confidence: 99%
“…However, these HRQoL instruments often include mental illness and mental wellness indicators which raises the question—to what degree is the absence of mental disorder symptoms equal to a high degree of mental wellness? As such, we argued that more instruments need to be developed in LMICs to give insight into which constructs of mental wellness are important to improving overall mental wellbeing for adolescents living in these contexts (Orth and van Wyk, 2021a ; Orth et al, 2022 ). Though there was a lack of clear definition of mental health, we identified 13 mental wellness concepts from 79 instruments, namely: life satisfaction, mental wellbeing [general], resilience, self-efficacy, self-esteem, connectedness, coping, self- control, mindfulness/spiritual, hope, sense of coherence, happiness, and life purpose (Orth et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…As an analytical approach, DA is aimed at analysing language in relation to the social context, focusing on how meaning is created in different social contexts. 21 Therefore, this analytic process allowed us to interrogate and explore how mental wellness was discussed, positioned, and constructed by adolescent participants who were living with HIV and on treatment. Two researchers (the authors) were involved in the data analysis process.…”
Section: Methodsmentioning
confidence: 99%
“…This helped us to develop a preliminary framework of mental wellness concepts. 21 , 22 We also familiarised ourselves with the context of the healthcare facilities by conducting interviews with key healthcare workers. 19 This allowed us to develop an understanding of the real-life context of the discourse which emerged from the photovoice groups.…”
Section: Methodsmentioning
confidence: 99%
“…Before setting out to develop a new instrument, it is necessary to determine if one is needed or if existing instruments may be used [1,2]. To this end, we conducted a systematic review of mental health instruments used in research with adolescents [25,26]. A key nding from the systematic review, highlighted that there is a lack of consensus around de nitions of mental wellness for adolescent.…”
Section: ) Identifying the Gapmentioning
confidence: 99%